Money-back guarantees in individual pension accounts: Evidence from the German pension reform - Raimond H. Maurer; Christian Schlag (Goethe University Frankfurt, Center for Financial Studies (CFS), 2002)
The German Retirement Saving Act instituted a new funded system of supplementary pensions coupled with a general reduction in the level of state pay-as-you-go old-age pensions. In order to qualify for tax relief, the providers of supplementary savings products must offer a guarantee of the nominal value at retirement of contributions paid into these saving accounts. This paper explores how this 'money-back' guarantee works and evaluates alternative designs for guarantee structures, including a life cycle model (dynamic asset allocation), a plan with a pre-specified blend of equity and bond investments (static asset allocation), and some type of portfolio insurance. We use a simulation methodology to compare hedging effectiveness and hedging costs associated with the provision of the moneyback guarantee. In addition, the guarantee has important implications for regulators who must find an appropriate solvency system for such saving schemes.
urn:nbn:de:hebis:30-9932
Keywords: G11; G23; G28; 330; Pension Finance; Shortfall Risk; Long Term Investment; Regulation